Teacher professional knowledge and development for reflective and inclusive practices - Amzat, Ismail Hussein (Routledge, 2017)
This book brings together the practice of reflective teaching and the knowledge of inclusive practices in the context of teacher education and continuing professional development. It is a call to leverage reflective teaching for inclusive practices. The first part of the book provides an overview of what constitutes reflective practice in the 21st century and how teachers can become reflective practitioners. It also discusses how teacher professional development can be enhanced for reflective teaching practice. The second part of the book deals with teachers' knowledge development in order to create inclusive teaching and learning environments. It highlights the need for a responsive teaching climate, intercultural competency, pedagogical change and professional literacy. A reflective inclusive teacher is likely to anticipate the multiple needs of diverse learners in pluralistic settings, thus ensuring student success. This book will enhance the efforts of teacher educators and teaching professionals in building a culture of reflective and inclusive teaching practice in the classroom.